Design and optimization of mRNAs encoding an Anti-TIGIT antibody with therapeutic potential for cancer in TIGIT-humanized BALB/c Mice - Cui, Jingmin; Qiaerxie, Gulisaina; Qin, Hui; Long, Feng; Wang, Xi; Yang, Zhixin; Du, Peng; Cui, Yong (Archives of Pharmacy and Pharmaceutical Sciences, 2023)
mRNA drugs are synthesized using cell-free systems without complex and stringent manufacturing processes, which makes their preparation simple, efficient, and economical. Over the past few years, mRNAs encoding antibodies have been one of the research frontiers of antibody drug development. In cancer immunotherapy, mRNAs encoding immune checkpoint antibodies may be advantageous regarding antibody persistence and durability of the anti-tumor immune response of patients. In our previous study, a candidate antibody—AET2010—targeting the novel immune checkpoint TIGIT was reported. Its anti-tumor activity was also investigated using adoptive transfer of NK-92MI cells in a xenograft mouse model, but the limitations of the model did not facilitate precise evaluation. In the present study, we further investigated the therapeutic potential of AET2010 for cancer in TIGIT-humanized BALB/c mice. Next, we explored the design, synthesis, and optimization of mRNAs encoding AET2010 and ultimately obtained a candidate mRNA (mRNA-BU) with favorable in vitro and in vivo expression levels of active AET2010. Particularly, lipid-nanoparticle-encapsulated mRNA-BU delivered to mice produced AET2010 with significantly higher peak concentration and expression duration than an equivalent dose of original AET2010. This study provides a sound basis for developing novel drugs targeting TIGIT.